2016
DOI: 10.1002/ejsp.2192
|View full text |Cite
|
Sign up to set email alerts
|

When being far away is good: Exploring how mortality salience, regulatory mode, and goal progress affect judgments of meaning in life

Abstract: Research indicates that death‐relevant thoughts (mortality salience) have a nuanced effect on judgments of life's meaningfulness. Thoughts of death diminish meaning in life only among people who lack or do not readily engage psychological structures that confer meaning. Building on this past research, the current research examined how an important source of meaning, long‐term goal progress, affects the ways that death‐relevant cognitions impact judgments of life's meaning. In Study 1 (N = 118), mortality salie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…It is possible that possessing or pursuing an extrinsic goal generates meaning for individuals high in narcissism but achieving these goals does not. Such a finding would be consistent with recent research indicating that feeling further from attaining a goal preserves meaning following an existential threat, whereas feeling closer to attaining a goal does not (Vess, Rogers, Routledge, & Hicks, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that possessing or pursuing an extrinsic goal generates meaning for individuals high in narcissism but achieving these goals does not. Such a finding would be consistent with recent research indicating that feeling further from attaining a goal preserves meaning following an existential threat, whereas feeling closer to attaining a goal does not (Vess, Rogers, Routledge, & Hicks, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also shown that death-related cognition can affect the judgment of sense of life meaning, [22] and fear of death and avoidance of death are important independent determinants of the experience of sense of life meaning. [23] The meaning of life is revealed when the reality of inevitable death is accepted [24], and studies of older adults have shown that older adults with a strong sense of meaning are less likely to die during study follow-up [25]. This shows to some extent that it is necessary to guide college students to have a correct understanding of death to enhance the sense of meaning of life.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies on self‐regulation focused on the effect of the locomotion mode on various behaviors (Amato et al, 2016; Crow et al, 2019; Di Santo et al, 2018; Kruglanski, Pierro, & Higgins, 2007; Kruglanski et al, 2009; Kruglanski et al, 2016; Pica et al, 2015; Pierro, Giacomantonio, Pica, Kruglanski, & Higgins, 2013; Vess et al, 2017). For example, Amato et al (2016) found that high locomotors perform more extensive job searches and are likely to have more job interviews and job opportunities, resulting in employment.…”
Section: Studymentioning
confidence: 99%